The Predictive Potential of the Baseline C-Reactive Protein Levels for the Efficiency of Immune Checkpoint Inhibitors in Cancer Patients: A Systematic Review and Meta-Analysis - Han, Cheng-Long; Meng, Guang-Xiao; Ding, Zi-Niu; Dong, Zhao-Ru; Chen, Zhi-Qiang; Hong, Jian-Guo; Yan, Lun-Jie; Liu, Hui; Tian, Bao-Wen; Yang, Long-Shan; Xue, Jun-Shuai; Li, Tao (Frontiers in Immunology, 2022)
Abstract Background: The relationship between baseline C-reactive protein (CRP) level and the prognosis of cancer patients receiving immune checkpoint inhibitors (ICIs) treatment remains controversial. The aim of this meta-analysis was to clarify whether baseline CRP level can serve as a biomarker to predict the efficiency of ICIs therapy. Methods: All associated articles published in the Cochrane Library, EMBASE, and PubMed databases from the inception of the database to Dec 30, 2021 were retrieved. Progression-free survival (PFS) and overall survival (OS) outcomes were meta-analyzed using the random-effects model, and adjusted using the trim and fill method because of publication bias. Results: 33 studies (6124 patients) conducted between 2013 and 2021 were identified. The pooled outcomes implied that high baseline CRP level patients had significantly worse OS (adjusted pooled value for univariate and multivariate analysis outcomes: HR=1.48, 95% CI=1.41-1.56; HR=1.46, 95% CI=1.34-1.59) and PFS (adjusted pooled value for univariate and multivariate analysis outcomes: HR=1.29, 95% CI=1.15-1.45; HR=1.20, 95% CI=1.02-1.40) than low baseline CRP level patients, irrespective of cancer or ICIs type. Further analysis indicated that 1 mg/dl was appropriate as a cut-off value for determining low or high level of baseline CRP to predict the OS or PFS of cancer patients receiving ICIs treatment (Univariate analysis: HR=1.56, 95% CI=1.24-1.97, P=0.909; Multivariate analysis: HR=1.58, 95% CI=1.23-2.03, P=0.521). Conclusions: High baseline CRP level (>1 mg/dl) may be an indicator for worse OS and PFS of cancer patients treated with ICIs. More high-quality prospective studies are warranted to assess the predictive value of CRP for ICIs treatment.